Measurement of sensitivity of solar blind UV cameras to solar light - Chrzanowski, Krzysztof; Safiej, Bolesław (Opto-Electronics Review, 2021)
Solar blind UV cameras are not theoretically supposed to be sensitive to solar light. However, there is practically always some sensitivity to solar light. This limited solar sensitivity can sometimes make it impossible to detect the weak emission of a corona target located on the solar background. Therefore, solar sensitivity is one of the crucial performance parameters of solar blind UV cameras. However, despite its importance, the problem of determining solar sensitivity of solar blind UV cameras has not been analysed and solved in the specialized literature, so far. This paper presents the concept (definition, measurement method, test equipment, interpretation of results) of measuring solar sensitivity of solar blind UV cameras.